2011
DOI: 10.4103/0973-1482.92019
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of acetic acid comparing with conventional Pap smear in the detection of colposcopic biopsy-proved CIN

Abstract: Since diagnostic values of VIA is comparable to Pap smear, and it performs well in detecting a high grade lesion, we conclude that VIA can be used as a screening modality for cervical cancer in low resource settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 8 publications
3
26
0
Order By: Relevance
“…12 Hegade D et al studied 225 cases and concluded that VIA and Pap sensitivity and specificity are almost comparable. 13 Shuchi et al compared 200 patients with VIA, VILI and Pap, concluded that VIA and VILI had sensitivity comparable to Pap smear and can therefore be a suitable potential alternative/adjunctive screening test not only in resource-poor settings but also in well-equipped centers.…”
Section: Resultsmentioning
confidence: 99%
“…12 Hegade D et al studied 225 cases and concluded that VIA and Pap sensitivity and specificity are almost comparable. 13 Shuchi et al compared 200 patients with VIA, VILI and Pap, concluded that VIA and VILI had sensitivity comparable to Pap smear and can therefore be a suitable potential alternative/adjunctive screening test not only in resource-poor settings but also in well-equipped centers.…”
Section: Resultsmentioning
confidence: 99%
“…4 An abnormal Pap smear prompts a colposcopic examination with biopsies of abnormal-appearing cervical tissue. 5 It is common practice to use a three-step procedure involving cytology, colposcopy and histopathology to diagnose CIN, colposcopydirected multiple biopsy sampling being the key step. 6 However, the accuracy of this technique is highly dependent on the skill of the colposcopist; colposcopy-based diagnosis of CIN may be associated with a false-positive diagnosis leading to unnecessary hysterectomy, 7 or to a false-negative diagnosis G He, H Li, H Lin et al…”
Section: Introductionmentioning
confidence: 99%
“…In Eventually, the sensitivity of cytology in well established settings is over 80% [46,47]. And so the main prerequisite to shift from cytology to HPV testing-that sensitivity of conventional Pap testing is only around 50%-simply is not true.…”
Section: Resultsmentioning
confidence: 99%